Development Of Antibody Immobilisation Strategy Using Recombinant Human Neonatal Fc Receptor - Ng, Woei Kean (2017)
Antibody immobilisation is the cornerstone of antibody-based assay in biosensing technology which is predominantly used to detect and measure a wide variety of biological analytes, ranging from antigens, biomarkers, allergens and drug substances. As such, specific interactions between antibody and ligands are therefore needed to guarantee highest reproducibility and sensitivity possible. The complexity of pinning antibodies forms the key factor in interfering the outcome of an assay as the recognition molecule, i.e. the antibody itself, may have undergone structural changes and distortion when it is attached to the solid phase.